Sustainable Surveillance of Neglected Tropical Diseases for the Post-Elimination Era. (14th June 2021) - Hatherell, Hollie-Ann; Simpson, Hope; Baggaley, Rebecca F; Hollingsworth, T Déirdre; Pullan, Rachel L
Abstract: The World Health Organization's (WHO's) 2030 road map for neglected tropical diseases (NTDs) emphasizes the importance of strengthened, institutionalized "post-elimination" surveillance. The required shift from disease-siloed, campaign-based programming to routine, integrated surveillance and response activities presents epidemiological, logistical, and financial challenges, yet practical guidance on implementation is lacking. Nationally representative survey programs, such as demographic and health surveys (DHS), may offer a platform for the integration of NTD surveillance within national health systems and health information systems. Here, we describe characteristics of DHS and other surveys conducted within the WHO Africa region in terms of frequency, target populations, and sample types and discuss applicability for post-validation and post-elimination surveillance. Maximizing utility depends not only on the availability of improved diagnostics but also on better understanding of the spatial and temporal dynamics of transmission at low prevalence. To this end, we outline priorities for obtaining additional data to better characterize optimal post-elimination surveillance platforms.